Ogimah Ikwe: Native Women and Their Path to Leadership - Lajimodiere, Denise K. (Wicazo Sa Review, 2011)
Much documentation gathered on Native American women's activities originated in the journals of European male missionaries and explorers. These first visitors observed Native societies through the eyes of their own culture, a culture in which male activities were the only happenings of note. 1 This bias led to indirect and distorted descriptions of Native American women's activities and beliefs. 2 Scholars who study Native American women today have made significant inroads into their histories; however, many interpretations remain incorrect and undeveloped. Devon Mihesuah states, "Because many authors write from a patriarchal or white feminist perspective, the value of Indian women is vastly underrated." 3 Gretchen Bataille and Kathleen Sands address this shortcoming, saying, "The portrayal of American Indian women in North America over the last four centuries offers an uneven body of documentary evidence about the lives of Native women as individuals and members of their group." This study's purpose is to increase the visibility of Native American women in leadership roles by recording the voices and histories of nine Native American women leaders. It focuses on the experiences, perceptions, and beliefs of the women interviewed, giving a voice to nine of today's Native American female leaders, nine Ogimah Ikwe (leader women).
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cours; discipline; discours dominant; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; histoire et politique; patriarcat; pol4105; premier cycle; premières nations; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; travail; états-unis

Law Reform, Lesbian Parenting, and the Reflective Claim - Leckey, Robert (Social & Legal Studies, 2011)
The article aims to complicate efforts to make law fit or catch up to social practices. It scrutinizes the ‘reflective claim’ using the case study of recognition of parenting by lesbian couples. Reforms in the United Kingdom’s Human Embryology and Fertilisation Act 2008 and the Canadian province of Quebec’s civil code are compared with empirical work from the social sciences on lesbians’ family practices. The reflective claim rests on problematic ideas about social practices and law. Since law is always blunt and incomplete, choices must be made as to which practices it should aim to recognize. Furthermore, the impact of heterosexist and homophobic conditions on lesbian families means that observable practices may not be a suitable model for gay-affirmative reforms. As advanced in the literature, the reflective claim overlooks law and society’s complex interaction, including how reform will not merely reflect but also alter practices. It fails to do justice to law reform’s normative character, obscuring its costs and positive potential
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; angleterre; approches et analyses; canada; corps; cours; discipline; discours dominant; droit; droit des femmes*; europe; hétérosexisme; identités LGBTQIA2+; inégalités; maternité; parentalité; premier cycle; périodes historiques; queer; québec; régions géographiques; science politique et droit; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

Luttes XXX : inspirations du mouvement des travailleuses du sexe - Mensah, Maria Nengeh; Toupin, Louise; Thiboutot, Claire (Les éditions du remue-ménage, 2011)
Depuis 1973, des travailleuses et travailleurs du sexe aux quatre coins de la planète se regroupent et se mobilisent. Qui sont ces personnes, comment s’organisent-elles et pourquoi revendiquent-elles la décriminalisation de leur travail? Qu’ont-elles à dire à propos du syndicalisme, du féminisme, de la lutte contre le sida, de la violence ou des phénomènes migratoires? Tout en situant le mouvement des travailleuses du sexe dans son contexte historique et international, cette anthologie unique propose une sélection de documents inédits ou traduits en français pour la première fois. Luttes XXX nous invite à la rencontre d’un mouvement social méconnu. Ici, les voix des travailleuses et travailleurs du sexe, longtemps réduites au silence, s’élèvent, réclament justice.
Keywords: anthologie; approches et analyses; cours; discours dominant; droits des femmes*; fem1000; international; inégalités; justice sociale; mouvements sociaux; premier cycle; santé; systèmes d'oppressions; thématiques; travail; travail du sexe; témoignage

Changing the framework: Disability justice - Mingus, Mia (Leaving Evidence, 2011)
Pendant mon travail de justice sociale, j'ai découvert que le handicap est quelque chose que la plupart des gens connaissent très peu - et cela inclut des organisateurs et des militants communautaires chevronnés, féroces et très respectés. Les gens considèrent généralement le handicap comme un défaut ou un problème individuel, plutôt que comme quelque chose en partie créé par le monde dans lequel nous vivons. Il est rare que les gens pensent au handicap comme une expérience politique ou comme englobant une communauté pleine d'histoires, de cultures et d'héritages riches. .
Keywords: approches et analyses; capacitisme; corps; cours; discours dominant; fem3300; identités LGBTQIA2+; inégalités; justice sociale; personnes handicapé.e.s*; premier cycle; queer; ressource en ligne; systèmes d'oppressions; thématiques

Moving toward the ugly: A politic beyond desirability - Mingus, Mia (Leaving Evidence, 2011)
*Femmes Of Color Symposium Keynote Speech, Oakland, CA (8/21/11)
Keywords: approches et analyses; capacitisme; corps; cours; discours dominant; fem3100; identités LGBTQIA2+; premier cycle; privilèges; queer; racisme; ressource en ligne; sexisme; sexualité; systèmes d'oppressions; thématiques

La chasse aux Musulmans : évincer les Musulmans de l'espace politique - Razack, Sherene (Lux éditeur, 2011)
Trois personnages emblématiques caractérisent la guerre contre le terrorisme : le « dangereux » Musulman, la Musulmane « en péril » et l’Européen « civilisé ». Le présent ouvrage étudie la manière dont ces trois figures sont utilisées pour créer une véritable fable, celle d’une grande famille de nations occidentales qui s’estiment contraintes d’employer la force, tant militaire que politique et juridique, pour se protéger contre la « menace » des populations du tiers-monde. Sherene Razack montre qu’on entretient délibérément cette fable pour justifier l’expulsion des Musulman.e.s de l’espace politique, en les stigmatisant d’abord, puis en les plaçant sous surveillance, en les emprisonnant, en les torturant, ou en larguant des bombes sur leurs pays. Dans cet essai d’une grande actualité, Sherene Razack explique de quelle façon la « pensée raciale » – logique qui divise le monde entre cielles qui méritent d’être protégés par les lois et cielles qui ne le méritent pas – nous habitue à l’idée qu’il est nécessaire et légitime, pour des raisons de sécurité nationale, de suspendre les droits de certains groupes racialisés. L’autrice montre aussi que le refus de reconnaître une même nature humaine chez les peuples d’ascendance européenne et ceux qui ne le sont pas a favorisé l’implantation et la prolifération de « camps », au sens propre et figuré, c’est-à-dire de lieux où les libertés fondamentales sont bafouées et les lois ignorées.
Keywords: 2000 à aujourd'hui; approches et analyses; cours; discours dominant; fem3400; histoire et politique; personnes musulmanes; premier cycle; périodes historiques; racisme; système colonial; systèmes d'oppressions; thématiques; violences

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres